COMMUNITY EMPOWERMENT THROUGH THE DEVELOPMENT OF COLLECTIVE AEROFARM-BASED VEGETABLE CULTIVATION IN CISAUK VILLAGE - Agustine, Dine; Amyranti, Mutia; Maftukhah, Siti (LPPM Univ. Ibn Khaldun Bogor, 2022)
Aeroponics is a method of cultivating plants without using soil. Aeroponics is generally used for cultivating vegetable types. Community service in the form of counseling on the development of AeroFarms vegetable cultivation and the manufacture of aeroponic plants in Pabuaran village, Cisauk sub-district, Tangerang district, Banten province, is motivated by the lack of use of technology as a means that can help fulfill daily needs even as employment and community economic improvement. This activity aims to provide knowledge about environmentally friendly technology that is easy for the residents, namely the development of aeroponic plant cultivation, and provide knowledge about creativity in farming to the community and utilizing natural resources around. The material contains an understanding of aeroponics, the history of aeroponics, various aeroponic methods, stages of aeroponic planting, and the advantages of using aeroponic methods. The implementation of AeroFarms-based collective vegetable cultivation development activities can create community creativity, become a solution for the conversion of agricultural land and can maintain and improve household food security.